The Influence of Reproductive Health Education to Knowledge and Percieved Behavior Sexual Adolescent Control - Kumalasari, Nurya; Kuswardinah, Asih; Deliana, Sri Maryati (Universitas Negeri Semarang, 2020)
Teenage is a phase that ranges with delinquency especially sexuality. Sexuality which is still considered a taboo makes the lack of knowledge and low perceived behavior control in adolescents so that more teenagers have had sexual relations before marriage. Premarital sexual behavior has an impact on health, that is transmission of sexualy transmitted diseas/infections and teenage pregnancy which can result in dropping out of school, other social sanction or complications during pregnancy, childbirth, and peurperial. The purpose of this study was to analyze the effect of reproductive health education on knowledge and perceived behavior control. This research was conducted using quasi-eksperimental one group pretest-posttest design. Population of this study was student grade XI SMA in Grobogan with number of sample was 85 student. Data analizing were using Wilcoxon Test. There was a difference level of knowledge with a p-value of 0,000; there was differences in the behavior of the Perceived Behavior Control with a p-value of 0,000 and there was an influence between the knowledge and Perceived Behavior Control with a p-value of 0,000 after health education. There was a difference between the knowledge and behavior of Perceived Behavior Control after health education.